Soil health strategies for sorghum systems in Kenya: A training of trainers field manual - Kinyua, Michael; Mulei, Welissa; Kihara, Job; Mandlenkosi, Nkomo (2023)
The Excellence in Agronomy (EiA) Initiative offers a new model and research culture, seizing these opportunities to deliver agronomic gain at scale by facilitating efficiencies through globalized networking and aligning research and development (R&D) priorities with demands from scaling partners through context-specific Use Cases. It utilizes standardized analytics and decision support approaches in partnership with non-CGIAR Advanced Research Institutes (ARIs) and builds on Use Cases involving multi-actor partnerships. The vision of success of EiA is to deliver by 2030 agronomic gain for millions of smallholder farming households in prioritized farming systems, with emphasis on women and young farmers for measurable impact on food/nutrition security, income, water use, soil health and climate resilience. EiA’s delivery pathway is through facilitating the delivery of agronomy-at-scale solutions, including development and technical/user-experience validation and the co-creation and deployment of gender- and youth- responsive solutions to smallholder farmers via scaling partners; Enabling the creation of value from big data and advanced analytics through the assembly and governance of data and tools, application of existing analytics and solutions for specific use cases, supply of information on climate impacts, inclusivity and sustainability of agronomic solutions; and national agricultural research system capacity strengthening; Driving the next generation of agronomy- at-scale innovations by addressing key knowledge gaps and facilitating innovation in agronomy research through engagement with partners, and Nurturing internal efficiencies for an agile and demand-driven agronomy research and development community through internal organization and external partnerships for prioritization, demand mapping and foresight.